Antioxidant, anticoagulant and mosquitocidal properties of water soluble polysaccharides (WSPs) from Indian seaweeds. (September 2019) - Venkatesan, Manigandan; Arumugam, Velusamy; Pugalendi, Rubanya; Ramachandran, Karthik; Sengodan, Karthi; Vijayan, Sri Ramkumar; Sundaresan, Umamaheswari; Ramachandran, Saravanan; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Water Soluble Polysaccharides (WSP) were extracted from three Indian seaweeds. WSP contained high glucose, protein, moisture and essential mineral content. WSP demonstrated commendable antioxidant, anticoagulant and mosquitocidal activities. Abstract: Water Soluble Polysaccharides (WSP) from three selected Indian seaweeds were extracted and fractionated by Ion Exchange Chromatography (IEC) to yield fractionated polysaccharides (FPs). Structural characterization of the FPs was performed using FT-IR and UV-Visible spectroscopy and the antioxidant properties were evaluated by total antioxidant, 2, 2 diphenyl-1-picrylhydrazyl (DPPH) and Hydrogen Peroxide radical scavenging (H2 O2 ) assays. FPs from Gracilaria filiforms demonstrated higher glucose, protein, moisture and essential mineral compositions. FPs from Gracilaria filiforms also exhibited higher scavenging activities in all the antioxidant assays. FPs from all the three seaweeds exhibited commendable anticoagulant activities. FPs from Gracilaria filiforms exhibited the maximum larvicidal activity on Anopheles stephensi (LC50 = 0.255867 mg/L) followed by Turbinaria conoides on Aedes aegypti (LC50 = 0.174348 mg/L) and Enteromorpha compressa on Culex quinquefasciatus (LC50 = 0.11175 mg/L). The results strongly establish the potentials of the FPs from the three selected Indian seaweeds as alternate functional foods and nutraceutical entities as well as mosquitocidal agents in future.